Increased Mechanical Stability and Thermal Conductivity of Alumina Reticulated Porous Ceramics (RPC) by Nanoparticle Infiltration Processing. Issue 10 (9th June 2017) - Rannabauer, Stefan; Söffker, Gerrit‐Maximilian; Scheunemann, Marcel; Betke, Ulf; Scheffler, Michael
Abstract : Infiltration processing of reticulated porous alumina ceramics (RPC) from reticulated foam manufacturing is investigated by micro computed tomography. Infiltration is carried out with colloidal alumina slurries. Successful infiltration is found to be a function of the RPCs starting microstructure and the particle size of the alumina in the colloidal infiltration system. Suitable infiltration conditions are specified. As a result, RPCs with a low relative density show a fivefold compressive strength after infiltration, as compared to their non‐infiltrated RPC counterparts. The highest strength of infiltration processed alumina RPCs at a porosity of 90% is found to be 1.6 MPa, and besides a significant increase of the compressive strength, the thermal conductivity is improved to be 1.5 W m −1 K −1 after infiltration. Abstract : Infiltration of RPC with colloidal alumina slurries is investigated with respect to the colloidal particle size. Classifying the RPCs' pore system into different pore orders, the distribution of the colloidal particles is examined by micro computed tomography. The infiltration results in a significant improvement of the struts and thereby the RPC.